The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ajps.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Advances in photosensitizer-related design for photodynamic therapy

Abstract: Photodynamic therapy (PDT) is highly effective in treating tumors located near body surface, offering strong tumor suppression and low damage to normal tissue nearby. PDT is also effective for treating a number of other conditions. PDT not only provide a precise and selective method for the treatment of various diseases by itself, it can also be used in combination with other traditional therapies. Because PDT uses light as the unique targeting mechanism, it has simpler and more direct targeting capability tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…It was found by Gierszewski et al [38] that porphyrazines with eight peripheral isophtaloxyalkylsulfanyl substituents generate singlet oxygen with Φ ∆ values between 0.01 and 0.04 in DMF and that incorporating Mg 2+ ions into the Pzs improves their capability to generate single oxygen. The exchange of Mg 2+ (3,6) to Zn 2 (4, 7) in the tribenzoporphyrazine ring influenced the singlet oxygen generation quantum yield values, which increased from 0.05 (3) to 0.24 (4) and from 0.20 (6) to 0.59 (7). In Figures 7 and 8, the Q-bands of 6 and 7 demonstrate only minimal to no changes during irradiation, thus indicating their good stability during measurements.…”
Section: Singlet Oxygen Generation Studymentioning
confidence: 95%
See 2 more Smart Citations
“…It was found by Gierszewski et al [38] that porphyrazines with eight peripheral isophtaloxyalkylsulfanyl substituents generate singlet oxygen with Φ ∆ values between 0.01 and 0.04 in DMF and that incorporating Mg 2+ ions into the Pzs improves their capability to generate single oxygen. The exchange of Mg 2+ (3,6) to Zn 2 (4, 7) in the tribenzoporphyrazine ring influenced the singlet oxygen generation quantum yield values, which increased from 0.05 (3) to 0.24 (4) and from 0.20 (6) to 0.59 (7). In Figures 7 and 8, the Q-bands of 6 and 7 demonstrate only minimal to no changes during irradiation, thus indicating their good stability during measurements.…”
Section: Singlet Oxygen Generation Studymentioning
confidence: 95%
“…Metal-free Pz derivative 5 (92 mg, 0.075 mmol), N,N-dimethylformamide (DMF, 25 mL), and zinc(II) acetate (41 mg, 0.225 mmol) were stirred in a round-bottomed flask under inert gas at 70 • C for 24 h. After that, the solvent was evaporated, and the residual blue oil was subjected to column chromatography (dichloromethane/methanol 50:1 then 20:1), leading to a cerulean blue product 6 (79 mg, 71% yield). R f = 0.71 (dichloromethane/methanol, 20:1, v/v (7) Lithium aluminum hydride (13 mg, 0.353 mmol) was suspended in tetrahydrofuran (THF) precooled to 0 • C and stirred for 30 min. Porphyrazine derivative 6 (95 mg, 0.074 mmol) was dissolved in THF (14 mL), and the solution was added dropwise to the reaction mixture over 40 min.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Has been carried out by combining second-generation photosensitizers with receptor molecules to the desired target, such as proteins or lipoproteins that are used by pathogenic cells for their proliferation, monoclonal antibodies targeting a specific antigen of the target cell, surface markers such as, growth factors, hormones, or transferrin receptors ( Muehlmann et al, 2014 ; Zhang et al, 2018 ). These strategies allow greater delivery of the photosensitizer to the target tissue, that is, greater selectivity, which improves the effectiveness of PDT, in addition to decreasing the doses needed for desired therapeutic responses ( Calixto et al, 2016 ; Zhou et al, 2021 ).…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Still, some studies have also demonstrated that inorganic PS can be targeted to specific tissues, which represents a great advantage in its use for photodynamic therapy. 12 …”
Section: Introductionmentioning
confidence: 99%